Pengaruh Literasi Keuangan, Overconfidence, dan Toleransi Risiko terhadap Keputusan Investasi (Studi Kasus pada Generasi Z) - Nurhalisa M; Pristin Prima Sari; Johannes Maysan Damanik (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to analyze the effect of financial literacy, overconfidence, and risk tolerance on investment decisions among Generation Z in Yogyakarta. Using a quantitative approach, primary data were collected through a structured questionnaire distributed online via social media platforms such as WhatsApp, Instagram, and Twitter. The respondents consisted of Generation Z individuals actively investing in Yogyakarta. Data analysis was conducted using IBM SPSS 27.0. The results show that financial literacy has a positive and significant effect on investment decisions, indicating that higher financial knowledge enhances the quality of investment choices. Similarly, overconfidence also exerts a positive and significant influence, suggesting that Generation Z investors with high self-confidence in their financial knowledge tend to make bolder investment decisions, often influenced by easy access to information and personal experience. In contrast, risk tolerance does not have a significant impact on investment decisions, implying that a high willingness to take risks does not necessarily translate into more aggressive investment behavior. Simultaneously, financial literacy, overconfidence, and risk tolerance collectively have a significant effect on investment decisions, highlighting that investment behavior is shaped by a combination of financial knowledge and psychological factors. These findings underscore the importance of financial education and awareness of behavioral biases in supporting sound investment practices among young investors.